Beyond anthropomorphism: Odissi and the botanical. Issue 2 (1st October 2012) - Gardner, Sally
Drawing on experiences that have entailed watching and learning forms of so-called 'Indian dance' (Bharata Natyam and Odissi), and watching Odissi dancers performing in various locations in Orissa's 'sacred triangle' (Puri, Konark, Bhubaneswar), and against my own background in contemporary dance, I propose that the difference of the Odissi body is that the dancer dances with his or her feet in more than one kingdom – that is, he or she maintains a link between human bodies and the bodies of plants. Such a perception can help to displace questions of the dancer's spatiality and representations, challenging western or westernized visions of the industrial or mechanical body, assumed hierarchies of body parts and their signifying powers, and assumptions about the role of the joints. The sense of a botanical imaginary or specific cultural body-schema at work in Odissi dance is supported by discussion of historical and ethnographic literature pertaining to the (former) female dancers of the Jagannath Temple in Puri; the temple's links with Oriyan tribal cultures; the dancers' traditional importance according to an axis of social auspiciousness/inauspiciousness as opposed to social purity/impurity; and the particular processes of the reconstruction of Odissi dance (separate from that of Bharata natyam) after independence.